Arctic anticyclone and its influence on the North Atlantic Oscillation - Morozova S.; Denisov K.; Polyankaya E.; Chervyakov M.; Semenova N.; Ormeli E. (Russian Journal of Earth Sciences)
This article examines the influence of the permanent center of atmospheric action - the Arctic anticyclone (Arctic High) - on the dynamics of adjacent circulating oscillatory structures - the North Atlantic. Analysis of variance was used to estimate the degree of influence of the Arctic anticyclone on the state of the centers of action of the atmosphere in the North Atlantic. The influence of the Arctic High on the change in the pressure in the Icelandic minimum and Azores maximum is estimated at 48%. This influence showed not statistical significance, confirmed by Fisher's test. The impact of the circulation systems of the North Atlantic on the Arctic anticyclone is estimated at 7%, and is not statistically significant. A statistically significant correlation was found between the intensity of the Arctic High and the intensity of the Icelandic center of atmospheric action. With the strengthening of the Arctic anticyclone, the Icelandic depression deepen. The correlation coefficient were -0.39. This coefficient is statistically significant.